2019
DOI: 10.1155/2019/6182580
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Meat Quality and Shelf Life from Broilers Fed with Different Sources and Concentrations of Methionine

Abstract: A trial with different concentrations of DL-methionine (DLM) and DL-2-hydroxy-4-methylthiobutanoic acid (DL-HMTBA) in broiler feed was performed to investigate their effect on the meat quality parameters and the shelf life of breast fillet. In total, fillets from 210 male broiler chickens (Ross 308) were tested in seven groups with 30 animals each. Three different concentrations (0.04, 0.12, and 0.32%; on an equimolar basis) of either DLM or DL-HMTBA were added to a basal diet, summing up to seven treatment gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 67 publications
(102 reference statements)
5
29
0
Order By: Relevance
“…Drip loss is considered a relevant indicator for determining the quality of meat where excessive drip loss is not desired. Drip loss (%) decreased in MET group, consistent with previous studies reported that increasing Met supplementation positively impact drip loss in broiler meat [ 44 , 46 , 47 ]. Meat color is a characteristic of importance to consumer acceptability.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Drip loss is considered a relevant indicator for determining the quality of meat where excessive drip loss is not desired. Drip loss (%) decreased in MET group, consistent with previous studies reported that increasing Met supplementation positively impact drip loss in broiler meat [ 44 , 46 , 47 ]. Meat color is a characteristic of importance to consumer acceptability.…”
Section: Discussionsupporting
confidence: 90%
“…Meat color is a characteristic of importance to consumer acceptability. In general, dietary Met supplementation led to higher lightness and redness values in breast muscles and redness in thigh muscles, with similar results also observed in previous studies [ 16 , 46 ]. There is a fluctuation in the meat color values between the thigh and breast muscles of different groups, all were in the normal range for measures of good meat quality.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The colour of broiler meat is probably one of the most essential visual factors affecting the purchasing decisions of consumers in the market (Wideman et al, 2016). It depends on a large number of factors such as genotype, slaughter age, sex, housing condition, diet, pre-slaughter stress, and some muscle myopathies as white striping (Siekman et al, 2018;Albrecht et al, 2019;Qamar et al, 2019). Almasi et al (2015) reported that indoor treatment had a lower impact on breast meat than the outdoor system.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate values (2.5 and 1.5) were allowed. These data were used to calculate the sensory index ( SI ) for every fillet according to Albrecht et al. (2019a ).…”
Section: Methodsmentioning
confidence: 99%